From ancient to contemporary molecular eco-epidemiology of Chagas disease in the Americas (2014)
One of the best-studied populations with regard to Chagas disease is from the coastal area of northern Chile at the foot of the western Andean slopes. The extremely arid climate here generates rapid, spontaneous desiccation of buried bodies, arresting the decay process. The absence of rainfall then preserves these dried bodies (mummies) for millennia. The aim of the present study was to perform the first molecular paleoepidemiological study on a set of 43 mummified human remains from the Atacama Desert in Northern Chile in order to elucidate the transmission dynamics and determinants of ancient genotypes, to try to unravel the natural history of the Trypanosoma cruzi taxon and Chagas disease. Interestingly, TcBat, a recently described Discrete Taxonomic Unit, emerges as the plausible ancestor of T. cruzi. The findings herein presented allow us to present a plausible model of T. cruzi transmission in pre-Columbian civilisations.